Challenging Hegemonic Masculinity, Pursuing Gender Equity: Case Study of Male Muslim Leaders of Islamic Boarding Schools - Hayat, Edi (Department of Political Sciences, Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2021)
This article is about men’s role in promoting gender equity with case study of male Muslim leaders of Islamic boarding schools who involved in the mainstreaming of gender equity. Few of them, who have engaged in, have been playing an effective role in gender mainstreaming. They can challenge the root causes of gender inequity without being seen to disrupt the socio-cultural and religious setup. They understand the gender-biased cultural practices necessitate to be changed and have the capacity to intervene in those aspects of social construction considered inimical to gender equity. Besides, they have empowered personally because they have made gender equity as their strategic choice to be pursued. Although they have previously denied choosing the issue, they have gradually received it fully in their preoccupation. Their empowerment has consisted of three dimensions, tangible and intangible resources, agencies, and the power of achievement. Their effectiveness has additionally depended on their vantage point as leaders, to tackle the root causes rather than the symptoms of gender inequity. In this paper, I look in detail at their work and explore the lessons that can be taken and replicated elsewhere in the Islamic world for greater gender equity.